Direction‐ and Polarization‐Resolved Radiation of Coupled Plasmon Modes on Silver Nanowires. Issue 3 (23rd December 2021) - Sun, Zhiguang; Käll, Mikael; Fang, Yurui
Abstract : By modulating the propagation of surface plasmons on metal nanowires, it is possible to build integrated nanophotonic circuits for optical information processing. However, the applicability of this emerging technology is complicated by the fact that several plasmon modes with different propagation behavior can be launched by the same excitation source. Herein, it is shown that it is possible to distinguish such modes by polarization‐resolved Fourier‐space leakage radiation microscopy. Mode assignment of coupled plasmon modes on silver nanowires is achieved by establishing a one‐to‐one correspondence between experimental Fourier patterns and electrodynamics simulations of leakage radiation directionality and polarization orientation. The work highlights the complicated coupling and interference of plasmon modes on nanowire waveguides and presents a convenient methodology for on‐chip analysis of their mode‐specific excitation and propagation characteristics. Abstract : Coupled plasmon modes on silver nanowires are imaged by direction‐ and polarization‐resolved Fourier‐space leakage radiation microscopy. Combining experiments and simulations, mode assignment of the coupled plasmon modes is achieved by establishing a one‐to‐one correspondence between the Fourier patterns and the leakage radiation directionality and polarization orientation. This presents a convenient methodology for on‐chip analysis of plasmon modes on nanowire waveguides.